The Role of Generative Artificial Intelligence in Mathematics Assessment from Teachers’ Perspectives - Al-Shahrani, Abdulrahman Nasser (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to explore the role of generative artificial intelligence in mathematics assessment from the perspective of teachers. It employed the descriptive survey method, and the instrument used was a questionnaire consisting of (29) items developed by the researcher. The questionnaire was distributed to a random sample of (56) teachers drawn from a study population of (120) middle school mathematics teachers in the city of Dammam for the academic year (1446 AH). The results showed that the perceived role of generative artificial intelligence in mathematics assessment—according to the sample—achieved a mean score of (4.11 out of 5). Their assessment of its value and importance yielded a mean score of (3.88), while the obstacles to employing generative AI in mathematics assessment received a mean score of (3.49), all of which were rated as (high). Additionally, the findings revealed statistically significant differences at the (0.05) level between teachers’ views on the role of generative AI in mathematics assessment, attributed to the variable of years of experience, in favor of the group with (5–9 years) of experience. Based on the results, the researcher recommended providing programs and training sessions for mathematics teachers to enhance the use of generative AI in assessment, as well as educating parents about its role in mathematics assessment.